2022
DOI: 10.3389/fnut.2022.863519
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and Exposure Assessment of Insecticide Indoxacarb Residues in Vegetables

Abstract: Indoxacarb, a promising new generation insecticide, is gaining popularity among vegetable growers in West Bengal, India, for controlling a large number of insects. However, it may simultaneously also increase the risk of contamination in the edible portions of the vegetables. This study was planned to analyze the persistence behavior of indoxacarb in cabbages, tomatoes, and soil. Moreover, indoxacarb residue contents were estimated to assess both the dietary and soil ecological risks associated with the applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Wang et al (2022) monitored 37 pesticide residues in 268 litchi samples; up to 11 pesticides were positive simultaneously, and 96.6% of the samples contained at least two pesticides. It is well known that half-life is an important indicator of pesticide safety evaluation; Patra et al (2022) reported that indefencarb degrades rapidly in cabbage and tomato, with a half-life ranging between 1.55 and 2.76 days, and can be safely consumed after spraying for 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2022) monitored 37 pesticide residues in 268 litchi samples; up to 11 pesticides were positive simultaneously, and 96.6% of the samples contained at least two pesticides. It is well known that half-life is an important indicator of pesticide safety evaluation; Patra et al (2022) reported that indefencarb degrades rapidly in cabbage and tomato, with a half-life ranging between 1.55 and 2.76 days, and can be safely consumed after spraying for 1 day.…”
Section: Discussionmentioning
confidence: 99%
“…Pesticide degradation is strongly influenced by biotic (micro- and macroflora) and abiotic (environmental) variables (soil, water, temperature, solar energy, etc.). Wide variations in the degradation pattern of the chemicals may result from any modifications to these parameters [ 29 , 30 , 31 , 32 ]. In an experiment dealing with six different pesticides, including spinetoram in pak choi, it was reported that dissipation of the compounds was faster in open field conditions than in greenhouse conditions due to several environmental factors, including rainfall and sunlight.…”
Section: Discussionmentioning
confidence: 99%
“…Larvae were individually placed in new 25 mL transparent plastic containers with a small piece of net for perching. According to our pretrials, the recommended spraying dosage [32,33], and indoxacarb dissipation rate in the rice field [34,35], we set five gradient concentrations (0.008 mg/L, 0.04 mg/L, 0.2 mg/L, 1 mg/L, 5 mg/L), a control (CK) and solvent control (AC). A solvent control was tested because we first dissolved 10 mg of indoxacarb in 10 µL of acetone before dispersing it in aged tap water.…”
Section: Behavioral Experiments With Indoxacarb Treatmentsmentioning
confidence: 99%